2023
DOI: 10.3390/molecules28186669
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Recovery of Phenolic Compounds from Distilled Rosemary By-Product Using Green Extraction Methods: Optimization, Comparison, and Antioxidant Activity

Maria Irakli,
Adriana Skendi,
Elisavet Bouloumpasi
et al.

Abstract: Rosemary solid distillation waste (SWR), a by-product of the essential oil industry, represents an important source of phenolic antioxidants. Green technologies such as ultrasound-assisted extraction (UAE), microwave-assisted extraction (MAE), and accelerated solvent extraction (ASE) of phenolic compounds from SWR were optimized as valorization routes to maximize yield, rosmarinic acid (RMA), carnosol (CARO) and carnosic acid (CARA) contents. Response surface methodology was used in this context, with ethanol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Custodio et al [45] investigated the antioxidant activity of the extracts obtained by the decoction of various parts of the carob tree and found that the leaves showed the highest activity according to the FRAP and DPPH test, which can be attributed to the high polyphenolic content. Other studies [46,47] that compared the antioxidant activity of plant extracts using the above-mentioned methods also concluded that the highest antioxidant activity was shown by the extracts with the highest level of polyphenols. In order to investigate the effect of polyphenolic content in the optimal extracts obtained in this study and antioxidant activity, Pearson's correlation factors were calculated (Table 4).…”
Section: Antioxidant Activity Of the Carob Leaf Extractsmentioning
confidence: 95%
“…Custodio et al [45] investigated the antioxidant activity of the extracts obtained by the decoction of various parts of the carob tree and found that the leaves showed the highest activity according to the FRAP and DPPH test, which can be attributed to the high polyphenolic content. Other studies [46,47] that compared the antioxidant activity of plant extracts using the above-mentioned methods also concluded that the highest antioxidant activity was shown by the extracts with the highest level of polyphenols. In order to investigate the effect of polyphenolic content in the optimal extracts obtained in this study and antioxidant activity, Pearson's correlation factors were calculated (Table 4).…”
Section: Antioxidant Activity Of the Carob Leaf Extractsmentioning
confidence: 95%
“…Flavan-3-ols were only determined in the leaf extracts and epicatechin was present in higher contents. Contradictory results are reported in the literature concerning the extraction efficiency of phenolic compounds using ASE and MAE and some authors have concluded that the extraction method should be selected depending on the target molecules, as not all phenolics follow the same trend [70,71]. Biesaga [72] reported that hydroxyl groups promoted the degradation of flavonoids during MAE, while sugar and methoxyl groups protected them from degradation.…”
Section: Uplc/esi-msmentioning
confidence: 99%